IMMUNOHISTOCHEMICAL RESEARCH OF KIDNEY OF RATS WITH CONGENITAL AND ACQUIRED HYPOTHYROIDISM AND CONDITIONS HORMONE REPLACEMENT THERAPY - Kuzmenko, Y.Y.; Stechenko, L.A. (World of Medicine and Biology, 2016)
The article presents an analysis of immunohistochemical detection and localization of expression of nuclear antigen cell proliferative activity (РСNA) and the proapoptotic protein Вах in kidneys postnatal ontogenesis at different stages of the congenital and acquired hypothyriosis and L- thyroxine in the application and its combination with calcitonin. The study found that increasing the term shortage of thyroid hormones in rats with congenital and acquired hypothyroidism PCNA expression level in the kidney increases, especially at the stage of decompensation. The same applies to the expression Вах. Representative product PCNA expression in 100-days rats after thyroidectomy expressed to a much lesser extent than in animals treated with corrective means.